Aplikasi Internet Of Things Monitoring Kebun Hidroponik Model Nft Menggunakan Panel Solar - Khairunnisak, Khairunnisak; Rahmat, Rahmat (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2022)
The increasing conversion of land to non-agricultural land, especially in Indonesia, has resulted in the development of many agricultural models that no longer depend on large tracts of land or agricultural land. The current hydroponic model is one of the modern technologies that is easy to develop without relying on agricultural land. This is because hydroponics is an agricultural model that does not use soil as a growing medium, but plants are only fed with nutrient fluids through plant roots. Hydroponic gardens generally use a parallon type of pipe installation to drain nutrients by using a pump as the irrigation method. In addition, hydroponic gardens are also required to check nutrient levels regularly at 560-840 ppm. This is because sometimes ppm of nutrients will affect hydroponic plants if the number is outside this range. The problem is that the garden manager is required to control the nutrient levels 2 times a day, in the morning and evening, which is certainly very inconvenient for the garden manager. Therefore, in this study, the development of hydroponic garden monitoring technology based on IoT technology that can provide reports on nutrient levels via smartphones. The results of the research conducted are that the application developed is able to control the condition of the hydroponic garden in real time. In addition, through the use of solar panel technology, hydroponic gardens are also able to supply electricity for their operations without having to rely on electricity supply from PLN